Chemical Composition, Antibacterial and Antifungal Activity of the Essential Oil from Cistus ladanifer L. - Jamila El Karkouri; Mohamed Bouhrim; Omkulthom Mohamed Al Kamaly; Hamza Mechchate; Amal Kchibale; Imad Adadi; Sanae Amine; Souâd Alaoui Ismaili; Touriya Zair (Plants, 2021)
Cistus ladanifer L. is a plant widely used in folk medicine to treat various illnesses. This study aims to evaluate the effect of the plant flourishing time harvest on the chemical composition and the antimicrobial effect of its essential oil. Chemical analysis of the essential oil was carried out using gas chromatography-mass spectrometry (GC-MS). The antibacterial and antifungal proprieties were tested against four selected bacteria (Staphylococcus aureus, Salmonella Typhi, Escherichia coli, and Acinetobacter baumannii) and nine fungi (Yeasts (Candida tropicalis, Candida glabrata, Candida dubliniensis, Candida sp., Rhodotorula rubra, Cryptococcus neoformans) and molds (Penicillium sp. (P), Fusarium sp. (F), Aspergillus niger (A. niger)), respectively. The essential oil of C. ladanifer demonstrated a powerful antibacterial activity with an inhibition zone of 55 ± 0.22 mm for Staphylococcus aureus, 42 ± 0.11 mm for Escherichia coli, 35 ± 0.27 mm for Acinetobacter baumannii (Full resistant to antibiotics) and 30 ± 0.25 mm for Salmonella Typhi. It also inhibited all tested bacteria at 10 µL/mL. For the antifungal activity test, C. tropicalis and C. neoformans appeared to be the most sensitive strains to the essential oil with an inhibition zone of 13 mm, followed by R. rubra and Penicillium sp. (12 mm), then C. dubliniensis and C. glabrata (11 mm). The chemical analysis of the essential oil by GC-MS revealed that the major components of the essential oil were viridiflorol (17.64%), pinocarveol (11.02%), bornylacetate (9.38%), and ledol (8.85%). C. ladanifer exhibited a remarkable antimicrobial activity that could be more exploited to develop targeted natural remedies against specific diseases.